2019
DOI: 10.1097/mpg.0000000000002149
|View full text |Cite
|
Sign up to set email alerts
|

Severe Deoxyguanosine Kinase Deficiency in Austria

Abstract: Mutations in the nuclear gene DGUOK, encoding deoxyguanosine kinase, cause an infantile hepatocerebral type of mitochondrial depletion syndrome (MDS). We report 6 MDS patients harboring bi-allelic DGUOK mutations, of which 3 are novel, including a large intragenic Austrian founder deletion. One patient was diagnosed with hepatocellular carcinoma aged 6 months, supporting a link between mitochondrial DNA depletion and tumorigenesis; liver transplantation proved beneficial with regard to both tumor treatment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
0
13
1
Order By: Relevance
“…After screening titles and abstracts, 563 articles were retrieved for full-text evaluation. Ultimately, 67 non-overlapping studies [ 11 , 12 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ,…”
Section: Resultsmentioning
confidence: 99%
“…After screening titles and abstracts, 563 articles were retrieved for full-text evaluation. Ultimately, 67 non-overlapping studies [ 11 , 12 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ,…”
Section: Resultsmentioning
confidence: 99%
“…These cases, including ours, support LT in the absence of significant neurological abnormalities, for patients with DGUOK deficiency in liver failure. Additionally, the last case as well as ours received living‐related LT demonstrating that parents who may be carriers can also serve as donors 3 . Although the parents are the most readily available donors, and often the most willing to donate to their child, more distant relatives should be considered for alternatives and if possible unrelated donors 1 …”
Section: Discussionmentioning
confidence: 77%
“…Additionally, Waich et al reported a case of an infant with hepatocellular carcinoma who underwent living donor LT from her mother at 8 months of age, before the DGUOK diagnosis was made. At 36 months of age, the patient had normal psychomotor development 3 . These reports demonstrate that the symptoms alone are not sufficient to determine the outcome of LT as cases with neurological involvement had varied outcomes between no neurological deterioration, reversed neurological deterioration, severe neurological deterioration, and even death.…”
Section: Discussionmentioning
confidence: 89%
“…In addition to the two patients who initially presented with HCC in this study, three MPV17-deficient patients developed HCC 27,35,37 . HCC was also observed in DGUOK-deficient patients 19,29 . It is presumed that dNTP imbalance is associated tumorigenesis but much remains to be clarified about the association between carcinoma and MTDPS 40 VUS, variant of unknown significance; LT, liver transplantation Table 6.…”
Section: Discussionmentioning
confidence: 88%
“…However, no significant differences in body weight were noted between these two groups in the postnatal period, suggesting that MPV17-deficient patients had marked postnatal growth restrictions compared to non-MPV17 patients. Previous studies have reported that low birth weight was observed in 20-80% of patients with DGUOK mutations and also in patients with POLG mutations [15][16][17][18][19][20][21] . However, very few studies have reported MPV17-deficient patients exhibiting intrauterine growth restrictions (IUGR) 15,[21][22][23] .…”
Section: Discussionmentioning
confidence: 95%